ANALISIS KADAR LOGAM Pb (TIMBAL) DAN KANDUNGAN PROTEIN PADA TERITIP (Balanus. sp) DI PESISIR PULAU BUNYU KALIMANTAN UTARA - Annuary Laksono; Rudi Kartika; Noor Hindryawati (PROSIDING SEMINAR KIMIA, 2017)
The researched about “The Correlation Level of Metal Lead (Pb) Towards The Protein Content of Teritip (balanus. sp)” this research was taken In The Coastal Water of Bunyu Island, North Borneo “This research aims to know the level of Metal (Pb) and protein content of Teritip (balanus. sp) based on the size and location of the different sampling. Afterwards, The Lead (Pb) metal and protein are correlated using Least Square method. Analysis of Metal (Pb) content by using AAS (Atomic absorption Spectrofotometry) and analysis of protein content using Kjeldahl method. From this research, it is found the Pb metal ion levels on point 1 is by an average of 0,574 mg/L, On point 2 is by an average of 0,816 mg/L, On points 3 is by an average of 0,648 mg/L and point 4 is by an average of 0,569mg/ L . It is also found the content protein of Teritip (balanus. sp) on point 1 is by an average of 22,9447 %. On point 2, it is found the average of protein content of 27,5737 %, point 3 by an average of 24,1332 % and point 4 by an average 20,9972 % . The correlation of Pb Metal level towards protein conten on Teritip (balanus. sp) symbolized as R2 = 0,810. Keywords: Pb Metal, Protein, Teritip (balanus. sp)